2022
DOI: 10.3390/genes13091572
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the R2R3-MYB Gene Family in Theobroma cacao

Abstract: The MYB gene family is involved in the regulation of plant growth, development and stress responses. In this paper, to identify Theobroma cacao R2R3-MYB (TcMYB) genes involved in environmental stress and phytohormones, we conducted a genome-wide analysis of the R2R3-MYB gene family in Theobroma cacao (cacao). A total of 116 TcMYB genes were identified, and they were divided into 23 subgroups according to the phylogenetic analysis. Meanwhile, the conserved motifs, gene structures and cis-acting elements of prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In our study, we identified 124 R2R3-CnMYB genes, which exhibited a range of exon numbers from 1 to 16 ( Figure 3 ). Most of the R2R3-CnMYBs, similar to those found in other plant species, consisted of three exons and two introns ( Liu et al., 2014 ; Chen et al., 2022 ; Du et al., 2022 ). It is worth noting that within the same subfamily, the exon/intron patterns of R2R3- CnMYB genes showed remarkable, with the majority of genes having no more than two introns.…”
Section: Discussionsupporting
confidence: 70%
“…In our study, we identified 124 R2R3-CnMYB genes, which exhibited a range of exon numbers from 1 to 16 ( Figure 3 ). Most of the R2R3-CnMYBs, similar to those found in other plant species, consisted of three exons and two introns ( Liu et al., 2014 ; Chen et al., 2022 ; Du et al., 2022 ). It is worth noting that within the same subfamily, the exon/intron patterns of R2R3- CnMYB genes showed remarkable, with the majority of genes having no more than two introns.…”
Section: Discussionsupporting
confidence: 70%
“…The characteristic of PnTLPs, including protein length, isoelectric point (pI), molecular weight (MW) and grand average of hydropathicity (GRAVY) were predicted by ExPASy ProtParam (http://web.expasy.org/protparam/) (Liu, Cui, et al, 2020). The subcellular localization of proteins were predicted by the Bologna Uni ed Subcellular Component Annotator (BUSCA) website (http://busca.biocomp.unibo.it/) (Du, Zhang, et al, 2022).…”
Section: Identi Cation Of Pntlp Genes and Analysis Of Its Characteris...mentioning
confidence: 99%
“…The gene duplication of PnTLPs in P. notoginseng genome was performed by MCscanX with the default parameters, and circus was used to locate all the PnTLP genes on the P. notoginseng chromosome by Tbtools version 1.120 (Du, Zhang, et al, 2022). The syntenic relationships between the PnTLP genes and TLP genes from A. thaliana and O. sativa were obtained also using McscanX and both results visualized in Tbtools (Feng, Abubakar, et al, 2023).…”
Section: Gene Duplication and Collinearity Analysis Of Pntlp Genesmentioning
confidence: 99%
“…Multiple sequence comparison of the EfR2R3-MYB proteins and 126 Arabidopsis thaliana AtR2R3-MYB proteins was carried out using MEGA 7.0 software with the neighbor-joining method (NJ method) and a bootstrap value of 1000 to construct the phylogenetic tree [27,28].…”
Section: Phylogenetic Tree Analysismentioning
confidence: 99%